(untitled) (European Journal of Marketing and Economics, 2018)
This article explores the different determinants of the capital structure in the Moroccan stock market. Panel data regressions were used to investigate the capital structure determinants in Casablanca stock market during the period 2009 to 2013. All the regressions incorporated four major variables that have led to significant results. These variables are size, profitability, dummy variable for financials and growth. Moreover, a new variable related to ownership structure has been considered in this article. By introducing the ownership variable, we would test if firms hold by parent groups, which control bank subsidiaries, profit from easier access to debt. Different proxies will be defined for ownership such as continuous and dummy variables. The main finding is that the ownership variable is insignificant while using continuous or dummy variables. We observe that even by using several proxies, we still find insignificant levels. Moreover, all the coefficients for this variable present a negative sign. This means that the Moroccan firms owned by parents companies, that control bank subsidiaries, do not benefit from the easier access to debt. These results can be interpreted as a good signal of the governance of the Moroccan firms.